Implementation of English Language Teaching (ELT) Through Understanding Non-EFL Students’ Learning Styles - Tira Nur Fitria (Education Human and Development Journal, 2023)
This research investigates the non-EFL students9 learning styles and describes how to teach English with different learning styles. This research is descriptive qualitative research. The analysis shows that are six types of students9 learning styles including VAK (Visual, Auditory, and Kinesthetic), also the combinations of learning styles including visual-auditory, visual kinesthetic, and auditory kinesthetic. This also shows that students can have more than one learning style such as visual-auditory, visual-kinesthetic, and auditory-kinesthetic learning styles. Non-EFL students learning a language tend to apply a visual learning style. Students with a visual learning style more easily absorb information from the sense of sight, such as through pictures/images. While students with an auditory learning style easily understand when processing information through the sense of hearing (listening). On the other hand, students with a kinesthetic learning style need opportunities to be actively moving. Therefore, with understanding and the teacher’s knowledge of learning styles each student in the teacher’s class can implement interesting and meaningful English learning. Understanding the learning styles may be very helpful for students to learn via activities in the manner in which they learn best. It will assist students to comprehend the course material easily, so enhancing their motivation and language skills, enhancing their enjoyment of the learning process, reducing their stress levels, and resulting in higher performance. When the teacher understands students’ learning styles, teachers should provide interesting materials and an appropriate learning environment